THE EFFECTIVENESS OF POSTER MEDIA ON KNOWLEDGE AND SMOKING BEHAVIOR AMONG HIGH SCHOOL STUDENTS IN BANDA ACEH - Destari, Popi Lya; Tahlil, Teuku; Susanti, Suryane Sulistiana (Jurnal Perawat Indonesia, 2022)
Smoking behavior in adolescents is still very concerning as it becomes a detrimental habit that isconsidered common by several teenagers around the world. Health education is an effort to supportbehavior changes in adolescents, including in changing their smoking behavior. This study aimed todetermine the effectiveness of poster media on increasing knowledge and decreasing smoking behavioramong high school students in Banda Aceh. This quantitative study used a quasi-experimental design withone group pre-test and post-test design involving 106 respondents. The intervention program to providehealth education using the poster as a media was carried out for 3 weeks. The effect of the intervention onparticipants was assessed using a questionnaire and processed using the SPSS program. The resultsshowed that the use of posters was increasing the mean score of students' knowledge about the dangers ofsmoking (pre-test x ̅ = 15.57 and post-test x ̅ = 16.80, p-value = 0.000) and decreased behavior bad behaviorby 68.9%. About 28.3% bad behavior and 31.1% good behavior were changing into 71.7% good behavior.This means that there is a difference between the mean pre-test and post-test on smoking behavior (themean pre-test is 27.226 and the mean post-test is 33.679), with p-value = 0.000 <ɑ = 0.05. This indicatesthat health promotion using posters is effective and can be applied to increase knowledge and decreasesmoking behavior in high school students of Banda Aceh.Keywords: Health Education, Poster, Knowledge, Smoking Behavior